THE EFFECT OF PARENT-ADOLESCENT ATTACHMENT AND SIBLING RELATIONSHIP ON DECISION MAKING ABILITY - Nandini, Kingkin; Krisnatuti, Diah (Journal of Child, Family, and Consumer Studies, 2024)
Decision-making skills are one of the developmental tasks that adolescent need to require. Several factors that can influence adolescent decision-making abilities can come from parents and siblings. The aim of the research is to analyze the relationship and effect of parent-adolescent attachment and sibling relationship on decision-making abilities. This research uses quantitative methods with purposive sampling techniques and data collection is used by distributing questionnaires via the Google Form tool. This research involved 100 adolescents who had complete parents, siblings (older), and participated in school organizational activities in the city of Bogor. Adolescents' decision-making abilities are in the medium category, adolescents' attachment to their parents is in the medium category while interactions between siblings and older siblings are in the low category. Different test results show that boys have tend more impulsive decisions than girls. The results of the effect test show a positive influence on older sibling's age, older sibling status, and parent-adolescent attachment, while birth distance and extended family have a negative effect on adolescent decision-making ability. This means that adolescent who have older siblings, have older siblings who are at school or work, who closer the birth distance, the fewer family members, and the higher the parent-adolescent closeness will increase the adolescent's decision-making ability